Patterns of noise exposure and prevalence of hearing loss amongst Cape Town Minstrel Carnival musicians - Lebogang Ramma (South African Journal of Communication Disorders, 2021)
Background: Cape Town Minstrel Carnival is one of the oldest and most authentic indigenous New Year’s customs in South Africa. Musicians who perform at this carnival are exposed to excessively loud music and therefore at a risk of acquiring noise-induced hearing loss (NIHL).